BOOKS RECENTLY PUBLISHED. (Notes, 2011)
A bibliography on the subject of music is presented which includes the books "Taylor Swift," by Holly Cefrey, "Frank: The Voice," by James Kaplan, and "Chamber Music: A Listener’s Guide," by James M. Keller.